Maternal alcohol consumption in pregnancy enhances arterial stiffness and alters vasodilator function that varies between vascular beds in fetal sheep. (23rd May 2014) - Parkington, Helena C.; Kenna, Kelly R.; Sozo, Foula; Coleman, Harold A.; Bocking, Alan; Brien, James F.; Harding, Richard; Walker, David W.; Morley, Ruth; Tare, Marianne
<x xml:space="preserve">Abstract</x> Key points To date, the effects of maternal alcohol consumption in pregnancy have focused on neurodevelopmental outcomes, with the impact on the arterial system poorly understood. In this study we investigated the effects of moderate maternal alcohol consumption (∼3 standard drinks per day) in late pregnancy on the ability of arteries in the fetus to relax, and hence deliver blood, and on arterial stiffness in five important organs. Maternal alcohol consumption in late pregnancy resulted in a marked increase in stiffness in arteries of the heart, kidney, gut, leg muscle and brain in the fetus, and this could slow contraction and relaxation and overall blood delivery. Coronary artery endothelial vasodilator function was severely blunted as a result of alcohol exposure, while in contrast endothelium‐dependent relaxation in renal and mesenteric arteries was enhanced. Together, the results of this study provide a warning for pregnant women and their carers that maternal consumption of ∼3 standard drinks per day, levels that do not evoke physical abnormalities or growth restriction, can dramatically alter arterial function in the fetus. Abstract While the impact of alcohol consumption by pregnant women on fetal neurodevelopment has received much attention, the effects on the cardiovascular system are not well understood. We hypothesised that repeated exposure to alcohol (ethanol) in utero would alter fetal arterial reactivity and wall stiffness, key mechanisms leading to cardiovascular disease in adulthood. Ethanol (0.75 g (kg body weight)–1) was infused intravenously into ewes over 1 h daily for 39 days in late pregnancy (days 95–133 of pregnancy, term ∼147 days). Maternal and fetal plasma ethanol concentrations at the end of the hour were ∼115 mg dl−1, and then declined to apparent zero over 8 h. At necropsy (day 134), fetal body weight and fetal brain–body weight ratio were not affected by alcohol infusion. Small arteries (250–300 μm outside diameter) from coronary, renal, mesenteric, femoral (psoas) and cerebral beds were isolated. Endothelium‐dependent vasodilatation sensitivity was reduced 10‐fold in coronary resistance arteries, associated with a reduction in endothelial nitric oxide synthase mRNA (P = 0.008). Conversely, vasodilatation sensitivity was enhanced 10‐fold in mesenteric and renal resistance arteries. Arterial stiffness was markedly increased (P = 0.0001) in all five vascular beds associated with an increase in elastic modulus and, in cerebral vessels, with an increase in collagen Iα mRNA. Thus, we show for the first time that fetal arteries undergo marked and regionally variable adaptations as a consequence of repeated alcohol exposure. These alcohol‐induced vascular effects occurred in the apparent absence of fetal physical abnormalities or fetal growth restriction.